FARMERS WILLINGNESS TO ACCEPT (WTA) FOR SUBMERGENCE RICE VARIETIES AT FLASH FLOOD AND FLOOD PRONE AFFECTED RICE AREA - Manikmas, Made Oka A. (Indonesian Journal of Agricultural Science, 2012)
Farmers are rational in decision making process with respect to any introduced agricultural technology. Farmers may consider the economic sacrifices in term of additional cost and potential benefit or additional income before they accept and adopt the introduced technology. This study aimed to analyze farmerâs criteria and determine explanatory variables affecting farmerâs decision to accept or to adopt submergence tolerant (Sub-1) rice varieties at flash flood and flood prone affected rice area. The study was conducted in Indramayu District, West Java, and Kayu Agung District, South Sumatra. Contingent Valuation Method (CVM) that derived Willingness to Accept (WTA) approach was exercised to analyze explanatory variables that influence farmersâ willingness to accept introduced rice varieties. The results showed that the economic cost of flooding that damaged rice was about US$7.63 million in Kayu Agung and US$11.25 million in Indramayu in every wet season planting. Farmerâs criteria used in submergence tolerant varietal evaluation varied and location specific in nature. Most of explanatory variables used in the model were significantly influenced farmersâ WTA for submergence tolerant rice varieties such as: (1) availability of seed, (2) submergence tolerant for more than 14 days, (3) high yield, (4) proffer rice taste, (5) householdsâ income during normal year, (6) area planted during normal year, and (7) age of farm household head. The only indicator that did not significantly influence the farmersâ WTA for the Sub-1 rice varieties was farm household income during the flood year cropping.Abstrak Bahasa IndonesiaPetani cukup rasional dalam mengambil suatu keputusan yang terkait dengan teknologi introduksi. Petani selalu mempertim-bangkan korbanan ekonomi yang mereka keluarkan sebagai konsekuensi tambahan biaya dan potensi tambahan pendapatan sebelum mereka menerima dan mengadopsi suatu teknologi introduksi. Studi ini dimaksudkan untuk menganalisis faktor yang memengaruhi keinginan petani untuk menerima atau meng-adopsi varietas padi tahan rendaman (Sub-1) pada lahan yang mengalami banjir musiman atau lahan rawa lebak. Penelitian dilaksanakan di Kabupaten Indramayu, Jawa Barat, dan Kayu Agung, Sumatera Selatan. Contingent Valuation Method (CVM) yang menggiring keinginan petani untuk menerima atau menolak suatu teknologi introduksi, diterapkan untuk menganalisis peubah penjelas yang memengaruhi keinginan petani untuk menerima atau menolak padi tahan rendaman. Hasil penelitian menunjuk-kan bahwa biaya ekonomi yang ditimbulkan oleh kedua jenis rendaman pada lahan sawah sekitar US$7,63 juta di Kayu Agung dan US$11,25 juta di Indramayu pada setiap tanam padi di musim hujan. Kriteria yang digunakan petani dalam mengevaluasi varietas padi tahan rendaman bervariasi dan bersifat spesifik lokasi. Sebagian besar peubah penjelas yang digunakan dalam model secara nyata dan positif mampu menjelaskan keinginan petani untuk menerima dan mengadopsi varietas padi tahan rendaman, seperti: (1) ketersediaan benih, (2) varietas padi toleran rendaman sampai 14 hari, (3) hasil tinggi, (4) rasa sesuai dengan selera konsumen, (5) pendapatan rumah tangga petani pada tahun normal (tidak banjir), (6) area tanam pada tahun normal, dan (7) umur kepala rumah tangga petani. Satu-satunya peubah bebas yang tidak berpengaruh nyata terhadap keinginan petani untuk mengadopsi varietas padi Sub-1 adalah pendapatan rumah tangga petani pada tahun munculnya banjir dan merendam lahan sawah.